Assessment of some baryte ores from Northern Cross-River, Nigeria, for oilfield drilling fluid supplement - Debrah Memshima Oahimire; Victor Uchechi Ukaegbu; Joel Friday Ogbonna (Brawijaya University, 2021)
There is a very high demand for the American Petroleum Institute (API) grade baryte in Nigeria due to the continuous massive drilling in oil and gas fields. Considering the presumption that local baryte is of low quality, processed baryte is imported, leading to great national revenue losses. Some baryte deposits in the Northern Cross River, Nigeria were sampled and studied in field and laboratories, based on API standard requirements (2004 and 2010), to ascertain their suitability for use as weighting additive in drilling fluids. Furthermore, flame testing of the samples yielded yellowish-green flame indicating barium presence; X-ray diffraction (XRD) and X-Ray fluorescence (XRF) analyses confirmed the mineralogy and chemical composition of the samples, respectively. The results revealed the Specific Gravity, SG range of 4.37 to 4.52; concentration of alkali earth metals as calcium 8.40mg/kg to 62.10mg/Kg; the residue >75micron and particle sizes <6microns processed had normal range, respectively below 3% and 30%; and the samples’ BaSO4 %weightcomposition was over 90%. The chemical analysis indicated no significant undesired minerals. Galena gangue with baryte was observed in three locations though these could be easily beneficiated through physical separation. The tests and analyses result qualified the Northern Cross River baryte samples as high-grade API standard baryte, suitable for oilfield drilling fluid. Further estimation of the baryte reserves in this region was highly recommended, as this might proffer a substantial solution to the sustainable supply of excellent local quality drilling baryte in Nigerian oilfields.